IMPLEMENTATION OF DISABILITY-FRIENDLY DEVELOPMENT; A Study on the Efforts of the Banyuwangi Regency Government to Provide Equal Access to People with Disabilities - Rizka Nanda Aprilita; Hary Priyanto; Niko Pahlevi Hentika (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
People with disabilities still experience structural vulnerability due to limited accessibility and participation in development, despite the existence of policies that guarantee the fulfillment of disability rights. This condition demands the implementation of inclusive development based on cross-actor collaboration. This study aims to analyze the implementation of cross-actor collaboration in involving people with disabilities to support inclusive development in Banyuwangi Regency. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. Informants were determined purposively by involving elements of the local government, the legislature, people with disabilities, and supporting organizations. The results show that the implementation of cross-actor collaboration has been quite effective in building synergy between stakeholders, increasing access, and participation of people with disabilities. The impact of inclusive development has not fully met the needs of people with disabilities, especially in aspects of physical accessibility and substantive involvement in decision-making. The importance of strengthening collaborative commitment, clarifying technical regulations, and continuous evaluation mechanisms is crucial to realize equitable inclusive development.